2019
DOI: 10.1111/ffe.13001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclic hardening on fatigue performance of slide burnished components made of low‐alloy medium carbon steel

Abstract: The slide burnishing process causes cyclic loading of the surface being treated, which provokes cyclic hardening. Using a forced‐controlled indentation test, the sixth “loading‐unloading” cycle was stabilised. The effect of the number of passes and the cyclic loading coefficient (CLC) on the fatigue performance of slide burnished specimens was investigated. Rotating bending fatigue tests were conducted using nine groups of hourglass shaped specimens, which were slide burnished through a different number of pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Probably at n = 5, a stabilised cycle is reached, and the micro-hardness changes slightly for a further increase in the number of passes. Detailed information on achieving a stabilised cycle in the DB process is given in [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Probably at n = 5, a stabilised cycle is reached, and the micro-hardness changes slightly for a further increase in the number of passes. Detailed information on achieving a stabilised cycle in the DB process is given in [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is found that the breaking strength increases along with the increase in hardness. This can be explained by the fact that the passage of ball under pressure piles up the superficial layers giving a structure with elongated grains [35]. Initially, this phenomenon improves the hardness at the surface and consequently increases the tensile strength of superficial layers.…”
Section: Overall Effect Of Burnishing On "W" "Hv" and "Rm"mentioning
confidence: 99%
“…Maximov and al. [35] noted that SB caused a fibrous micro structure of superficial layers characterized by grain refinement and elongation. The authors noticed an increase in fatigue limit of 40% when SB is performed with optimal parameters and n = 6 passes.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental studies of SB mainly focused on studying the SI obtained (85%), while the performance of SB-treated specimens occupies only 10% of the studies, of which 46% concern fatigue behavior, i.e., only 4.6% of the studies are devoted to the fatigue behavior of the components processed via SB [3]. The effect of SB on the fatigue strength of steel specimens was investigated by: Aliev and Aslanov [47] for stainless steel, Korzynski et al [48] for 42CrMo4 steel, Korzynski et al [49] for 42CrMo4 and 41Cr4 steels with chromium coatings, Maximov et al [40] for 42Cr4 steel, Maximov et al [50] for 37Cr4 steel, Swirad [51] for 40HM steel and Maximov et al [2] for AISI 316Ti steel. As can be seen, there are no studies devoted to 41Cr4 steel without chromium coating.…”
Section: Literary Surveymentioning
confidence: 99%
“…As can be seen, there are no studies devoted to 41Cr4 steel without chromium coating. In [50], the specimens were slide burnished with base parameters r = 3 mm , F b = 300 N , f = 0.05 mm/rev and v = 100 m/min , which are optimal under the "minimum roughness" criterion. It was found that with these basic parameters, the maximum fatigue limit (10 7 -cycle fatigue strength) was achieved using six passes.…”
Section: Literary Surveymentioning
confidence: 99%